2021
DOI: 10.1016/j.cgh.2020.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy-Related Mortality in a Fecal Immunochemical Test–Based Colorectal Cancer Screening Program

Abstract: 172,797 participants underwent colonoscopy after a positive result from a FIT in the Dutch national CRC screening program; 13,848 participants received a diagnosis of CRC. The reported fatal complication rate was 0.23 per 10,000 FITpositive participants (or 1 per 43,199; 95% CI, 0.090 -0.60) undergoing colonoscopy, whereas this was 0.91 per 10,000 FIT-positive participants (or 1 per 10,961; 95% CI, 0.44 -1.38) according to the excess death rate. Likely colonoscopy-related causes of death were reported in 0.86 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…First, Kooyker et al 1 suggest that because of the compliance to invitation for colonoscopy at the level of around 16% we were not powered to detect significant shift in mortality. This is not fully accurate; our primary goal was to assess the impact of a screening program as a populational intervention.…”
Section: Dear Editormentioning
confidence: 97%
See 2 more Smart Citations
“…First, Kooyker et al 1 suggest that because of the compliance to invitation for colonoscopy at the level of around 16% we were not powered to detect significant shift in mortality. This is not fully accurate; our primary goal was to assess the impact of a screening program as a populational intervention.…”
Section: Dear Editormentioning
confidence: 97%
“…In a recently published study Kooyker et al 1 analyze postcolonoscopy 30-day mortality facilitating data from a 2-step Dutch colorectal cancer (CRC) screening program. On a substantial study sample of more than 3.7 million persons the authors compare fecal immunochemical test (FIT)-positive screenees undergoing screening colonoscopy with FIT-negative control subjects that did not undergo colonoscopy.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…37 The Dutch screening program estimated the colonoscopy-related mortality to be 0.23-0.91 per 10,000 colonoscopies. 38 In an evaluation of the Stockholm-Gotland gFOBT screening program, there were no deaths related to colonoscopy, and all complications of bleeding and perforation were related to polypectomy. 39 Complications are rare, especially after a diagnostic colonoscopy, and the benefit of screening seems to outweigh them.…”
Section: Post Current Strategy Nmentioning
confidence: 98%
“…Mortality after colonoscopy has been rarely reported in literature and is expected to be underreported in adverse event registries. [22] A recent ASGE review reported a range of colonoscopy-related death rates from 0.002% to 0.011%. [20] To fully appreciate our findings, some limitations need to be addressed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%